Whole Organ Tissue Vascularization: Engineering the Tree to Develop the Fruits - Pellegata, Alessandro F.; Tedeschi, Alfonso M.; De Coppi, Paolo (Frontiers in Bioengineering and Biotechnology, 2018)
Tissue engineering aims to regenerate and recapitulate a tissue or organ that has lost its function. So far successful clinical translation has been limited to hollow organs in which rudimental vascularization can be achieved by inserting the graft into flaps of the omentum or muscle fascia. This technique used to stimulate vascularization of the graft takes advantage of angiogenesis from existing vascular networks. Vascularization of the engineered graft is a fundamental requirement in the process of engineering more complex organs, as it is crucial for the efficient delivery of nutrients and oxygen following in-vivo implantation. To achieve vascularization of the organ many different techniques have been investigated and exploited. The most promising results have been obtained by seeding endothelial cells directly into decellularized scaffolds, taking advantage of the channels remaining from the pre-existing vascular network. Currently, the main hurdle we need to overcome is achieving a fully functional vascular endothelium, stable over a long time period of time, which is engineered using a cell source that is clinically suitable and can generate, in vitro, a yield of cells suitable for the engineering of human sized organs. This review will give an overview of the approaches that have recently been investigated to address the issue of vascularization in the field of tissue engineering of whole organs, and will highlight the current caveats and hurdles that should be addressed in the future.